Married By Accident (MBA) in The Community of Kampung Simpangan - Kusumay Saroh; Nanik Rahmawati; Rahma Syafitri (Social Issues Quarterly, 2023)
The changing times due to modernization are affecting people's lives. The amount of information about promiscuous sexual behavior that enters society without social control causes many teenagers to engage in promiscuity, resulting in pregnancies out of wedlock. This often forces them to marry or get Married By Accident. The aim of this research is to find out how families respond to marriages outside of marriage or marriages by accident. The method used in this research is qualitative research with a descriptive approach. Data was obtained through observation, interviews, and documentation. The sampling technique used was purposive sampling. The criteria for informants in this study were teenagers and parents who had accidentally married. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The results of the research show that there has been a social change in the Simpang Village community. The family's response to getting married accidentally was characterized by anger, disappointment, sadness, and shame due to the family's disgrace. Therefore, the marriage was carried out to remove the shame and responsibility of the man who had impregnated the woman. Social change in the Simpang Village community has led to social functions and dysfunctions. Latent functions are considered as hidden and unexpected functions, and manifest functions are considered as real or expected functions. Marriage by accident has latent or hidden functions, namely eliminating shame, covering family disgrace, preventing slander, and being responsible for the man who has impregnated the woman. Meanwhile, dysfunction is due to social changes caused by marriages due to accidents, such as getting pregnant out of wedlock, which is a family disgrace and has become a taboo thing that has become commonplace in society.